If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-5w + 5) * 3w = 5(w + -5) + -53 Reorder the terms: -4(5 + -5w) * 3w = 5(w + -5) + -53 Reorder the terms for easier multiplication: -4 * 3w(5 + -5w) = 5(w + -5) + -53 Multiply -4 * 3 -12w(5 + -5w) = 5(w + -5) + -53 (5 * -12w + -5w * -12w) = 5(w + -5) + -53 (-60w + 60w2) = 5(w + -5) + -53 Reorder the terms: -60w + 60w2 = 5(-5 + w) + -53 -60w + 60w2 = (-5 * 5 + w * 5) + -53 -60w + 60w2 = (-25 + 5w) + -53 Reorder the terms: -60w + 60w2 = -25 + -53 + 5w Combine like terms: -25 + -53 = -78 -60w + 60w2 = -78 + 5w Solving -60w + 60w2 = -78 + 5w Solving for variable 'w'. Reorder the terms: 78 + -60w + -5w + 60w2 = -78 + 5w + 78 + -5w Combine like terms: -60w + -5w = -65w 78 + -65w + 60w2 = -78 + 5w + 78 + -5w Reorder the terms: 78 + -65w + 60w2 = -78 + 78 + 5w + -5w Combine like terms: -78 + 78 = 0 78 + -65w + 60w2 = 0 + 5w + -5w 78 + -65w + 60w2 = 5w + -5w Combine like terms: 5w + -5w = 0 78 + -65w + 60w2 = 0 Begin completing the square. Divide all terms by 60 the coefficient of the squared term: Divide each side by '60'. 1.3 + -1.083333333w + w2 = 0.0 Move the constant term to the right: Add '-1.3' to each side of the equation. 1.3 + -1.083333333w + -1.3 + w2 = 0.0 + -1.3 Reorder the terms: 1.3 + -1.3 + -1.083333333w + w2 = 0.0 + -1.3 Combine like terms: 1.3 + -1.3 = 0.0 0.0 + -1.083333333w + w2 = 0.0 + -1.3 -1.083333333w + w2 = 0.0 + -1.3 Combine like terms: 0.0 + -1.3 = -1.3 -1.083333333w + w2 = -1.3 The w term is -1.083333333w. Take half its coefficient (-0.5416666665). Square it (0.2934027776) and add it to both sides. Add '0.2934027776' to each side of the equation. -1.083333333w + 0.2934027776 + w2 = -1.3 + 0.2934027776 Reorder the terms: 0.2934027776 + -1.083333333w + w2 = -1.3 + 0.2934027776 Combine like terms: -1.3 + 0.2934027776 = -1.0065972224 0.2934027776 + -1.083333333w + w2 = -1.0065972224 Factor a perfect square on the left side: (w + -0.5416666665)(w + -0.5416666665) = -1.0065972224 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 8?-5=-40 | | 5(-4w+14)= | | c=d-f | | cx-10=-5forx | | -4(5x+7)=92 | | (x-2)(x+4)+6(x+2)(x-2)=x^2-4 | | 8+(-3)=9 | | [5h+2]=-8 | | 200=20x+100 | | 5(12k-17)= | | 77=17+6x | | 6n-6=6-5n | | 35x+x=3x+14 | | 6u-7=3 | | [2t-4]=8 | | 2(5x-8)-5(3x+5)=-5x | | 7x+8=3x+29 | | -2x+4=x+7 | | -6(6+5a)=-66 | | (-3)-2(x+6)=-5 | | -1=-.5x+2 | | 9w+33=3(w-9) | | 825+3.25x=8.20x | | X-(-2)=-6 | | -7y+5=4 | | 900=5e^9x | | (14x-5)+13x=180 | | -15=15q-50-5p | | (8x-1)(5x+1)=0 | | (5k+3)(k-2)=0 | | -6(3+2k)=-78 | | 5(5r+5)=-100 |